Primary Mathematical Modeling of the Growth of Diesel by a Bacterium Isolated from a Hydrocarbon-contaminated Soil - Rusnam, .; Syafrawati, S.; Rahman, Mohd Fadhil; Yasid, Nur Adeela; Nasution, Fachri Ibrahim; Yakasai, Hafeez Muhammad; Abubakar, Aisami (Journal of Environmental Microbiology and Toxicology, 2023)
Mathematical modeling of microbial growth via nonlinear regression is essential for determining key parameters such as the maximum specific growth rate, which are foundational for secondary modeling. Models such as modified Gompertz, modified Logistic, modified Richards, Buchanan-3-phase, Baranyi-Roberts, modified Schnute, von Bertalanffy, Morgan-Mercer-Flodin (MMF), and Huang elucidate the impact of substrates on bacterial growth and biotransformation processes, vital for biotechnological applications like wastewater treatment and bioremediation. A previously isolated diesel-degrading Pseudomonas sp. strain Neni-4 growth on diesel was modeled using the aforementioned primary models. Experimental data showed that diesel concentrations from 0.25 to 3.5% (v/v) are toxic, slowing bacterial growth and increasing lag periods from 3 to 15 hours. Among the primary models tested, the Baranyi-Roberts model provided the best fit, evidenced by a high adjusted coefficient of determination, low RMSE and AICc values, and favorable accuracy (AF) and bias factors (BF). The reliability of the Baranyi-Roberts model underscores its suitability for modeling bacterial growth under toxic conditions, offering valuable insights for optimizing biotechnological processes involving bacterial adaptation and growth under stress conditions.